The use of 3D model planning in the management of impacted teeth. (18th January 2018) - Scott, Jessica; Stagnell, Sami; Downie, Ian
Abstract: The extraction of deeply impacted mandibular wisdom teeth can be challenging and may pose a risk of damage to the Inferior Alveolar Nerve (IAN). Thorough planning helps minimise this risk whilst improving the efficiency of the surgical procedure. The use of modern imaging and modelling techniques can help mitigate this risk and improve outcomes. We discuss the case of a 61 year old male presenting to the outpatients department complaining of facial swelling and limited mouth opening. Plain film imaging revealed a deeply impacted molar with associated pathology. Subsequent 3D imaging provided more accurate location of the tooth and the close association with the IAN. Surgical planning included the construction of a 3D model of the mandible. A viewing window was created to observe both the tooth and nerve. The construction and customisation of the model allowed for practise surgery along with appropriate preoperative decision making. An acrylic guide was constructed to fit the mandible intraoperatively and guide the bone cuts in the correct position, relative to the unerupted tooth. The surgery was performed successfully using the guide intraoperatively. The tooth was removed without traumatising the IAN. The patient has since made a rapid and complete recovery after surgery with no neurosensory defect noted.